Mitigating lead acetate-induced histopathologic and physiologic disorders in rats receiving vitamin C and glutathione supplement - Mohamed Gaber Shalan (Heliyon)
The present work examines the extreme impact of lead acetate and the preventive function of co-supplementation with vitamin C and glutathione. It hypothesizes that these supplements can alleviate the poisonous effects of lead exposure. Eighty male albino rats, weighing 100 ± 15 g, were categorized into four groups: the control group, the second group receiving daily supplements of 100 mg/kg of body weight glutathione and 1 mg/100 g of body weight vitamin C orally, the third group receiving 100 mg/kg body weight of lead acetate orally daily, and the fourth group receiving similar oral dosages of lead acetate along with glutathione and vitamin C. Lead exposure significantly decreased body weight and relative testis weight, while relative organ weights for the liver, kidney, and spleen increased significantly. Additionally, lead acetate increased plasma glutamic pyruvic transaminase and glutamic oxaloacetic transaminase activities and plasma creatinine concentration (p < 0.05). Lead concentration rose significantly in blood, urine, liver, and kidney (p < 0.05). Examinations revealed that lead acetate exposure induced apoptotic DNA fragmentation in hepatocytes, significantly increasing caspase-3 activity (91 %) and annexin V indicators. Moreover, lead exposure induced a decrease in sperm count and motility, along with an increase in abnormal sperm morphology. However, vitamin C and glutathione supplementation significantly improved these adverse impacts, suggesting their protective function in counteracting the harmful impacts of lead acetate in different organs.